Enhanced Capacitive Energy Storage in Polyoxometalate‐Doped Polypyrrole. (4th May 2017) - Herrmann, Sven; Aydemir, Nihan; Nägele, Florian; Fantauzzi, Donato; Jacob, Timo; Travas‐Sejdic, Jadranka; Streb, Carsten
Abstract : High‐performance batteries and supercapacitors require the molecular‐level linkage of charge transport components and charge storage components. This study shows how redox‐tunable Lindqvist‐type molecular metal oxide anions [V n M 6– n O19 ] (2+ n )− ( M = W(VI) or Mo(VI); n = 0, 1, 2) can be incorporated in cationic polypyrrole (PPy) conductive polymer films by means of electrochemical polymerization. Electron microscopy and (spectro‐)electrochemistry show that the electroactivity and morphology of the composites can be tuned by Lindqvist anion incorporation. Reductive electrochemical "activation" of the Lindqvist–PPy composites leads to significantly increased electrical capacitance (range: ≈25–38 F g −1, increase up to ≈25×), highlighting that this general synthetic route gives access to promising capacitive materials with suitable long‐term stability. Electrochemical, electron microscopic, and Raman spectroscopic analyses together with density functional theory (DFT) calculations provide molecular‐level insight into the effects of Lindqvist anion incorporation in PPy films and their role during reductive activation. The study therefore provides fundamental understanding of the principles governing the bottom‐up integration of molecular components into nanostructured composites for electrochemical energy storage. Abstract : Capacitive energy storage is explored in Lindqvist–polyoxometalate/polypyrrole composites . The specific capacitance can be significantly increased using a reductive activation protocol, leading to promising new materials for electrochemical energy storage.